A new species of the rare Neotropical genus Auloceromyia Lindner, 1969 (Diptera: Stratiomyidae) and the first record of the male of A. pedunculata Pimentel & Pujol-Luz, 2000 - Fachin, Diego Aguilar (Zootaxa, 2015)
A new species of the Neotropical genus Auloceromyia Lindner—A. pachypoda nov. sp.—is described and illustrated based on one male from Argentina and twelve females from Mato Grosso do Sul State, Brazil. The male of A. pedunculata Pimentel & Pujol-Luz is described and illustrated for the first time, together with the first description of the female terminalia. A key to the known species of the genus is provided.